1991
DOI: 10.1021/ac00011a009
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization of porphyrins using a quadrupole ion trap for mass analysis

Abstract: The utility of electrospray (ES) Ionization combined with km trap mass spectrometry for the analysis of a wide variety of free-base porphyrins and metalloporphyrlns is examined. A single molecular Ionic species Is observed In most cases for the porphyrins under study. The free bases are detected as the protonated molecules, ( + H)+, the trlvalent metalloporphyrlns as (M -L)+, where L~Is a counteranion, and the divalent metalloporphyrlns as M*+, (M + H)+, and/or (M + Na)+, depending upon both the metal complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
117
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 50 publications
8
117
0
Order By: Relevance
“…ESI mass spectrometry is becoming a popular technique for the analyses of porphyrins and metalloporphyrins [10][11][12][13][14][15][16]. Free base porphyrins are readily protonated [14,16].…”
Section: Resultsmentioning
confidence: 99%
“…ESI mass spectrometry is becoming a popular technique for the analyses of porphyrins and metalloporphyrins [10][11][12][13][14][15][16]. Free base porphyrins are readily protonated [14,16].…”
Section: Resultsmentioning
confidence: 99%
“…Electrospray ionization (ESI) mass spectrometry (MS) is becoming a popular technique for the analyses of porphyrins [25][26][27][28][29][30][31][32][33][34][35].…”
mentioning
confidence: 99%
“…In particular, the Herpes simplex virus is one of the most common agents responsible for viral infections in man [5]. From preliminary virus inactivation studies carried out with Herpes simplex virus type 1 (HSV-1) using the cationic porphyrins 1 and 2 (Scheme 1), we have observed that despite their structural resemblance and their similar photocytotoxicity profiles, Compound 1 was very effective in the photoinactivation of the virus, whereas Compound 2 displayed no virucidal effect in the same conditions [6].Electrospray ionization mass spectrometry (ESI-MS) was successfully applied to characterize porphyrins as early as 1991 [7] and both ESI-MS [8 -11] and tandem mass spectrometry (ESI-MS/MS) [12,13] have been used to study neutral and cationic porphyrins since then. We wanted to know if the two porphyrin isomers, 1 and 2, could be differentiated by ESI-MS/MS and if the informa-…”
mentioning
confidence: 99%
“…Electrospray ionization mass spectrometry (ESI-MS) was successfully applied to characterize porphyrins as early as 1991 [7] and both ESI-MS [8 -11] and tandem mass spectrometry (ESI-MS/MS) [12,13] have been used to study neutral and cationic porphyrins since then. We wanted to know if the two porphyrin isomers, 1 and 2, could be differentiated by ESI-MS/MS and if the informa-tion obtained on their gas-phase behavior could be relevant to understand their virucidal properties.…”
mentioning
confidence: 99%